Membangun Konsep Teknis Aplikasi dan Pemanfaatan Metode dalam Penulisan Tugas Akhir Fakultas Ilmu Komputer - Sawali Wahyu; Jefry Sunupurwa Asri; Silvia Ratna Juwita; Adi Widiantono; Iksan Ramadhan (Publikasi Indonesia, 2023)
Community service activities organized by LPPM Esa Unggul University are carried out using webinars. This activity is a means of sharing knowledge for students of the Faculty of Computer Science regarding final assignments. The Final Assignment is a routine activity at the end of the semester carried out by students and their supervisors at the beginning of the preparation stage. Support for the final project concept can provide opportunities for students with their supervisors to hold discussions to find solutions to the problems of the research topics to be taken. In this abdimas scientific forum webinar, it was held to build concepts and technical applications in writing the final project for students of the Faculty of Computer Science. The result of this community service is to provide an overview of computer science faculty students in building concepts both in terms of application, methodology and writing procedures that are useful for preparing the final project. The Webinar presented several techniques and practices in making applications including: Introduction to Mobile Application Concepts and Methods, Data Management with Machine Learning, Compilation of Engineering Requirements and Creating Websites using the Code Igniter (CI) Framework. From the webinar material, it can help students explore topics and final project research concepts that will be carried out by students during the preparation of the Final Project.